Priorities for Conservation and Sustainable Use of Forest Genetic Resources in Four Mexican Pines - Andrés Flores (Forests, 2019)
The strategies for the conservation and sustainable use of forest genetic resources, which are essential for the future adaptation of forest species to changing environments, are also a source of valuable genetic resources for breeding and restoration activities. The first step to define and implement cost-effective strategies is to identify specific priority populations. Mexico, in spite of being characterized by high levels of tree species diversity, mostly lacks a combined strategy for the genetic conservation and use of forest genetic resources. The aims of this work are: (i) to identify areas for gene conservation, and (ii) to propose measures for the conservation and sustainable use of forest genetic resources of four pine species: Pinus greggii Engelm. ex Parl., Pinus oocarpa Schiede ex Schltdl., Pinus patula Schiede ex Schltdl. & Cham. and Pinus pseudostrobus Lindl. To do that, we use the existing information on the distribution, genetic variation and conservation and breeding efforts in Mexico. Overall, 51 areas for establishing genetic conservation units were prioritized and 6 genetic zones for the use of forest genetic resources in breeding and selection of forest reproductive material were identified. The current conservation efforts for the four priority Mexican pines should be improved to satisfy the needs of a national breeding and conservation network.